Evaluasi Kinerja Berbasis Aplikasi E-Kinerja Di Kantor Kecamatan Lubuk Sikarah Kota Solok - Elva Susanti; Hamidah Rahim; Sari Handayani; Ane Titisemita (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
E-Kinerja was created by the Minister of State Apparatus Empowerment which has been implemented at the State Personnel Agency since 2016. This digital-based system innovation was formed in order to make it easier for employees to input their daily performance results which are expected by appraisers to have convenience in supervising and assessing employee daily performance which has been listed in the State Civil Apparatus Act No. 5 of 2014. This study aims to be able to describe how employee performance analysis is produced by the existence of e-performance applications. The method used is a descriptive qualitative research. The location of this research is in Lubuk Sikarah, Solok City. The technique used by researchers in determining informants is purposive sampling technique with data collection techniques including interviews, observations and documents. While the data analysis technique used is data reduction, data presentation, and drawing conclusions. The results obtained from this study indicate that the analysis of employee performance based on the e-Kinerja application at the Lubuk Sikarah District Office has been said to be good, but there is still a need for improvement in terms of human resources, and support from superiors in order to create more effective and efficient performance.